CHROMOSOME CHARACTERIZATION OF THREE VARIETIES OF GINGER (Zingiber officinaleRosc.) - Budi Setiadi Daryono; Siti Nur Azizah Fauziati Rahma; Purnomo .; Sudarsono . (Indonesian Journal of Pharmacy, 2012)
Giant  ginger  (Zingiber  officinale Rosc.  var.  officinale),  red ginger  (Zingiber  officinale Rosc.  var.  rubra)  and  small  ginger (Zingiber  officinale Rosc.  var.  amarum)  are  three  varieties  of Zingiber officinale Rosc. They have a lot of benefit and often used by  Indonesian  as  a  traditional  drug.  Moreover,  they  have  a  big chance to be use as a flavor in world wide. Therefore, research for their  quality,  quantity  and  continuity  of  supplyare  needed. Characterization  of  their  chromosomes  is  one  effort for  improving ginger  cultivation.  The  objective  of  this  research  was  to  study mitotic  time  and  chromosome  characters  of  three  varieties  of ginger.  Squashing method was used for chromosome preparation. The  results  showed  that  mitotic  time  of  giant  ginger  is  09.00-10.05  am,  red  ginger  is  09.00-10.30  am,  while  small  ginger  is 08.45-11.00  am.  Chromosome  number  of  giant  ginger  and  small ginger are 2n=2x=30, while red ginger is 2n=2x=22. Giant ginger has R= 3,109, Red ginger has R = 3,206 and small ginger has R = 4,065.  Based  on  chromosome  characters  it  is  revealed  that relationship  between  giant  ginger  and  red  ginger  is  closer  that  of compare  to  small  ginger.  This  result  is  important  as  basic information for improving the gingers production through breeding program.Key  words:  Zingiber  officinale Rosc.,  mitotic  time,  chromosome characterization, squashmethod